Exact steering and stabilization of a PVTOL aircraft - Di Giamberardino, P.; Djemai, M.; Monaco, S.; Normand-Cyrot, D. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
A piecewise continuous control law for maneuvering a PVTOL aircraft is proposed. The control scheme is composed of two loops: a continuous inner state feedback one together with an outer piecewise constant one. The design procedure, based on some previous results on exact sampling and multirate techniques is briefly introduced and applied to our case study. An additional digital feedback is used to improve the robustness of the control scheme. Some simulation results are reported in order to show the effectiveness of the proposed control strategy.